Xenophobia in South Africa A History - Tafira, Hashi Kenneth (African Histories and Modernities, 2018)
This book is a vivid history of racism in post-apartheid South Africa, focusing on how colonialism still haunts black intraracial relationships. In 2008, sixty-four people died in a wave of anti-immigrant violence in the Alexandra township of Johannesburg; in the aftermath, Hashi Kenneth Tafira went to Alexandra and undertook an ethnographic study of why this violence occurred. Presented here, his findings reframe xenophobia as a form of black-on-black racism, unraveling the long history of colonial dehumanization and self-abnegation that continues to shape South African black subjectivities. Studying vernacular, popular stereotypes, gender, and sexual politics, Tafira investigates the dynamics of love relationships between black South African women and black immigrant men, and pervasive myths about male sexuality, economic competition, and immigrants. Pioneering and timely, this book presents a cohesive picture of the new face of racism in the twenty-first century.